ANALISIS DAMPAK SERTA PENGARUH GLOBALISASI EKONOMI TERHADAP RODA PEREKONOMIAN DI INDONESIA - Anan Subandi; Adam Farhanul Muttaqin; Sarip Hidayat; Rasidah Novita Sari (Publikasi Inspirasi Indonesia, 2023)
Economic globalization is the integration of a country's economy into the global economic system which is run by various parties such as multinational companies, the WTO. IMF and World Bank. Indonesia is dependent on international trade, production and finance from an economic perspective. This makes Indonesia vulnerable to pressure from the international level and the impact of globalization. The impact of economic globalization is felt in domestic economic law which must act as an integration tool to balance various internal interests of the country, national interests, as well as between sectors of life in the country. In the economic context there are various pressures on increasingly tight trade, production related to multinational companies, integration of financial markets and the inflow of global capital investment. To overcome the impact of economic globalization, it is important to use a proactive strategy in negotiations with parties involved in globalization. Besides that, creating national economic laws that regulate foreign investment can be a solution, by showing global interests to support domestic economic growth.